Formulation and Evaluation of Tablet using Latex Powder of Jatropha curcas as a Natural Binder - Sangramsinh Ghatage, Shitalkumar Patil, Ramling Patrakar, Sachinkumar Patil (Journal of Applied Pharmaceutical Science, 2015)
Purpose of this work was to evaluate binding efficiency of latex powder of Jatropha curcas in tablet dosage form. Tablets of BCS class I and II drugs Propoanolol hydrochloride and Oxcarbazepine respectively were prepared by wet granulation method. Various concentrations of latex powder of Jatropha curcas were tried for optimization of binder concentration. Tablets prepared were evaluated for weight variation, content uniformity, hardness, disintegration time, friability and drug release. Also tablet with standard binder Poly Vinyl Pyrolidone was prepared and compared with optimized formulations of natural binder. Tablets were successfully prepared by wet granulation method with all evaluation parameters well within official limits for all concentrations of binder for both the drugs. It has been observed that as concentration of binder increases hardness and disintegration time increases with decrease in friability and drug release. As compared with tablet prepared by standard binder, Poly Vinyl Pyrolidone, our optimized formulations have shown comparable results. The study revealed that latex powder of Jatropha curcus can be used as alternative binder than synthetic binders as it is cost effective and easily available.
Keywords: Latex powder of Jatropha Curcas,natural binder,tablet,Propranolol hydrochloride,oxcarbazepine.